A critical evaluation of the activity-regulated cytoskeleton-associated protein (Arc/Arg3.1)'s putative role in regulating dendritic plasticity, cognitive processes, and mood in animal models of depression - Li, Yan; Pehrson, Alan L.; Waller, Jessica A.; Dale, Elena; Sanchez, Connie; Gulinello, Maria (Frontiers in Neuroscience, 2015)
Major depressive disorder (MDD) is primarily conceptualized as a mood disorder but cognitive dysfunction is also prevalent, and may limit the daily function of MDD patients. Current theories on MDD highlight disturbances in dendritic plasticity in its pathophysiology, which could conceivably play a role in the production of both MDD-related mood and cognitive symptoms. This paper attempts to review the accumulated knowledge on the basic biology of the activity-regulated cytoskeleton-associated protein (Arc or Arg3.1), its effects on neural plasticity, and how these may be related to mood or cognitive dysfunction in animal models of MDD. On a cellular level, Arc is found to play an important role in modulating dendritic spine density and remodeling. Arc is also found to have a close, bidirectional relationship with postsynaptic glutamate neurotransmission, since it is stimulated by multiple glutamatergic receptor mechanisms but also modulates α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor internalization. The effects on AMPA receptor trafficking are likely related to Arc’s ability to modulate phenomena such as long-term potentiation, long-term depression, and synaptic scaling, each of which are important for maintaining proper cognitive function. Animal studies of chronic stress models of MDD show suppressed Arc expression in the frontal cortex but elevation in the amygdala. Interestingly, cognitive tasks depending on the frontal cortex are generally impaired by chronic stress, while those depending on the amygdala are enhanced, and antidepressant treatments stimulate cortical Arc expression with a timeline that is reminiscent of the treatment efficacy lag observed in the clinic or in preclinical models. However, pharmacological treatments that stimulate regional Arc expression do not universally improve relevant cognitive functions, and this highlights a need to further refine our understanding of Arc on a subcellular and network level.